Methoxypolyethylene glycol functionalized carbon nanotube composites with high permittivity and low dielectric loss. (July 2016) - Luo, Hang; Wu, Zhong; Chen, Chao; Ma, Chao; Zhou, Kechao; Zhang, Dou
Graphical abstract: Multi-walled carbon nanotubes (MWCNTs) were facilely modified by an amphiphilic polymer, the composites with modified MWCNTs exhibit high permittivity and suppressed dielectric loss. Abstract: High relative permittivity and low dielectric loss were simultaneously achieved in the percolative nanocomposites with methoxypolyethylene glycol (mPEG) modified multi-walled carbon nanotubes (MWCNTs). The dense mPEG layer with a thickness of approximately 1.7 nm was continuously coated on the surface of MWCNTs. MWCNTs exhibited excellent dispersibility after being functionalized by mPEG (mPEG@MWCNTs), the mPEG@MWCNTs/ethanol suspension was still turbid even when the suspension was deposited for two months. A high permittivity of 69.7 and a low dielectric loss of 0.042 were simultaneously achieved in the poly(vinylidene fluoride-co-hexafluoropropylene) (P(VDF-HFP)) nanocomposite with 4.02 vol% mPEG@MWCNTs at 1 kHz. The improved dielectric properties in the nanocomposite is mainly ascribed to the following reasons: (i) the increased microcapacitors formed by MWCNTs and insulated dielectric composite; (ii) the enhanced interfacial polarization due to the homogeneous dispersion of mPEG@MWCNTs in the nanocomposites and tight adhesion between mPEG@MWCNTs and P(VDF-HFP) matrix.